Improving maternal perinatal mental health: integrated care for all women versus screening for depression. (April 2013) - Laios, Lia; Rio, Ines; Judd, Fiona
Objective: The objective of this article is to highlight the debate about universal routine screening and psychosocial assessment in the perinatal period, and suggest an alternative/additional approach to improving maternal perinatal mental illness. Conclusions: Universal routine screening and psychosocial assessment in the perinatal period has been introduced in Australia despite a lack of evidence that this affects perinatal maternal morbidity. Furthermore, this approach is not designed to detect maternal illnesses such as schizophrenia, bipolar disorder, borderline personality disorder, although it is these women and their infants who have the highest rates of morbidity and mortality. We propose that any approach to improving maternal perinatal mental health should be tailored to particular situations and populations, with mental health care (inclusive of all mental illness, not just depression) integrated into, and thus a routine aspect of, maternity care provided to all women throughout the perinatal period.